The Sustainable Development Goals and Large Spanish Companies: An analysis of their commitment based on their Non-Financial Reporting - Domingo Martínez-Martínez; Paula Isabel Rodríguez Castro; Francisco Javier Andrades Peña; Jesús Sierra Blanco (Management Letters/Cuadernos de Gestión, 2024)
This paper aims to analyse the level of commitment with the SDGs of large Spanish companies based on the information published in their Non-Financial Statements and their letters from the chairman. To achieve this objective and identify potential explanatory factors, a balanced sample of 58 Spanish companies, 29 listed and 29 unlisted, in 2019 has been used. The results of this study evidence: i) the greater commitment with the SDGs of companies which are exposed in the stock markets and those which are larger; ii) the relevance of the diversity into the boards of directors, in order to integrate the largest and the widest number of interests as well as those values and principles which are intrinsically associated to women directors; and iii) the greater emphasis on those SDGs related to well-known issues by these organizations, thanks to their greater experience in non-financial reporting, publishing documents such as corporate social responsibility or sustainability reports.